Evaluation of immune responses induced by hydroalcoholic extract of Allium ampeloprasum. L subsp iranicum in mice: Allium iranicum as a powerful immune system booster - Shiehzadeh , Farideh; Vakili, Parham; Shirani , Kobra (Iranian Journal of Pharmaceutical Sciences, 2022)
The extract of some plants can play a role in modulating the function of the human immune system. Several studies have shown that Allium species can stimulate the immune system through different cellular mechanisms. In this study the effect of the hydroalcoholic extract of Allium ampeloprasum. L subsp iranicum on the immune responses of NMRI mice was investigated. Mice were randomly divided into three groups and each group was divided into four subgroups: normal saline, levamisole (20 kg/mg), A. Iranicum (150 kg/mg), and A. Iranicum (300 kg/mg). To evaluate immune responses, body and spleen weight, white blood cell count, delayed hypersensitivity response (DTH), antibody titer (HA), and lymphocyte proliferation test were used. A. Iranicum provoked several parameters including spleen weight, spleen cellularity, proliferation response to lipopolysaccharide (LPS) and phytohemagglutinin-A (PHA), HA titer, and DTH response. While A. Iranicum did not affect body weight and white blood cell counts. Considering the obtained results, it seems that the A. Iranicum can play an effective role in activating the immune system. To better understand the effect of the A. Iranicum on different cellular mechanisms of the immune system, further research is needed.